Prosody production networks are modulated by sensory cues and social context. Issue 4 (5th March 2018) - Klasen, Martin; von Marschall, Clara; Isman, Güldehen; Zvyagintsev, Mikhail; Gur, Ruben C; Mathiak, Klaus
Abstract: The neurobiology of emotional prosody production is not well investigated. In particular, the effects of cues and social context are not known. The present study sought to differentiate cued from free emotion generation and the effect of social feedback from a human listener. Online speech filtering enabled functional magnetic resonance imaging during prosodic communication in 30 participants. Emotional vocalizations were (i) free, (ii) auditorily cued, (iii) visually cued or (iv) with interactive feedback. In addition to distributed language networks, cued emotions increased activity in auditory and—in case of visual stimuli—visual cortex. Responses were larger in posterior superior temporal gyrus at the right hemisphere and the ventral striatum when participants were listened to and received feedback from the experimenter. Sensory, language and reward networks contributed to prosody production and were modulated by cues and social context. The right posterior superior temporal gyrus is a central hub for communication in social interactions—in particular for interpersonal evaluation of vocal emotions.